Solve the equation. e^2x - 6e^x + 5 = 0

Expert Answers info

justaguide eNotes educator | Certified Educator

calendarEducator since 2010

write12,544 answers

starTop subjects are Math, Science, and Business

We have to solve: e^2x - 6e^x + 5 = 0

e^2x - 6e^x + 5 = 0

let e^x = t

=> t^2 - 6t + 5...

(The entire section contains 61 words.)

Unlock This Answer Now



check Approved by eNotes Editorial


giorgiana1976 | Student

We'll apply substitution technique to solve the exponential equation.

e^x = t

We'll raise to square both sides:

e^2x = t^2

t^2 - 6t + 5 = 0

We'll apply quadratic formula:

t1 = [6+sqrt(36 - 20)]/2

t1 = (6 + 4)/2

t1 = 5

t2 = 1

But e^x = t1 => e^x = 5

We'll take natural logarithms both sides:

ln e^x = ln 5

x*ln e = ln 5

x = ln 5

e^x = t2=> e^x = 1

x = 0

The solutions of the equation are: {0 ; ln 5}.

check Approved by eNotes Editorial